2015
DOI: 10.5194/cpd-11-2847-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Did high Neo-Tethys subduction rates contribute to early Cenozoic warming?

Abstract: Abstract. The 58–51 Ma interval was characterized by a long-term increase of global temperatures (+4 to +6 °C) up to the Early Eocene Climate Optimum (EECO, 52.9–50.7 Ma), the warmest interval of the Cenozoic. It was recently suggested that sustained high atmospheric pCO2, controlling warm early Cenozoic climate, may have been released during Neo-Tethys closure through the subduction of large amounts of pelagic carbonates and their recycling as CO2 at arc volcanoes ("carbonate subduction factory"). To analyze … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Light blue bar indicates the timing of temperature and CO 2 decline after the EECO. Green light bar indicates the timing of potential circulation changes in the early Eocene, as demonstrated in the δ 13 C record of f. Overlying solid black and yellow bars represent the timing of volcanism [21][22][23][24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…Light blue bar indicates the timing of temperature and CO 2 decline after the EECO. Green light bar indicates the timing of potential circulation changes in the early Eocene, as demonstrated in the δ 13 C record of f. Overlying solid black and yellow bars represent the timing of volcanism [21][22][23][24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Kerrick and Caldeira (1994) suggested that carbon degassing due to metamorphism of Indian margin rocks along the Himalayan belt enhanced paleoatmospheric carbon levels, although revised estimates point to a minor contribution to early Eocene warming (Kerrick & Caldeira, 1998). A reduction of carbon dioxide emissions is inferred between~50 and 40 Ma, synchronous with the observed phase of climate cooling, when Tibetan arc volcanism was waning after collision between India and Eurasia (Hoareau et al, 2015;Jagoutz et al, 2016; Figure 1).…”
Section: Neo-tethys Closure and Associated Magmatismmentioning
confidence: 99%
“…The short‐lived magmatic flare‐up is in striking coincidence with the Early‐Eocene Climate Optimum, suggesting a cause‐effect relationship between the magmatic and climatic event, a possibility that was only marginally investigated thus far. Subduction of the carbonate‐rich Indian passive margin succession in the middle Paleocene may have enhanced carbon recycling at the Transhimalayan volcanic arc (e.g., Kent & Muttoni, ; van Hinsbergen et al, ; Hoareau et al, ). Hoareau et al () modeled the volume of subducted materials and the amount of CO 2 emitted along the northern Tethyan margin and the effects of estimated CO 2 fluxes on global climate.…”
Section: Solid Earth Control On Cenozoic Climate Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…1992; Rowley, 2002; Hoareau et al . 2015), compilation of zircon age (McKenzie et al . 2016), and reconstruction of the subduction zone length as a function of age (Van der Meer et al .…”
Section: The Source-side: Earth Co2 Degassing and Atmospheric Co2 Evomentioning
confidence: 99%